Optical–Physical Characteristics of Low Clouds and Aerosols in South America Based on Cloud-Aerosol Lidar and Infrared Pathfinder Satellite Observation - Bo Su; Dekai Lin; Ziji Liu; Qingyan Wu; Wenkai Song; Miao Zhang (Atmosphere)
Clouds and aerosols, as important factors in the Earth’s climate system, have significant impacts on the atmospheric environment and global climate. This study investigated the optical and physical properties of clouds and aerosols over South America from 2006 to 2021 using CALIPSO Level 2 products. South America was divided into four regions: A (Western Andean Mountains), B (Northern Orinoco and Amazon plains), C (Southern La Plata Plains), and D (Eastern Brazilian Highlands). Seasonal variations in the optical properties of low clouds and their interactions with the lowest-layer aerosols were analyzed and compared. The results indicate that Region C had the highest OPlc (probability of low clouds) and AODlc (AOD (Aerosol Optical Depth) of low clouds, likely due to its flat terrain and westerly influences. Both AODlc and OPlc were higher in September–November compared to other seasons. DRlc (depolarization ratio of low clouds) values were higher in Regions C and D, particularly in September–February, possibly due to topographic effects and more precipitation and higher humidity during this period. The elevated CRlc (color ratio of low clouds) in Region A may be attributed to the Andes blocking warm, moist air, leading to increased precipitation and cloud particle content. HLlc (top height of low clouds) and BLlc (base altitude of low clouds) were positively correlated with geographic elevation, while Tlc (thickness of low clouds) was greater at night, potentially due to enhanced atmospheric stability. Furthermore, strong correlations among certain parameters suggested significant interactions between aerosols and clouds.